Chemical constituents and antiplasmodial activity of indole alkaloids from ochrosia oppositifolia / Mehran Fadaei Nasab - Nasab, Mehran Fadaei (2012)
The chemical constituents of Ochrosia oppositifolia have been studied. The compounds were extracted from the bark and leaves of this plant by using n-hexane,dichloromethane and methanol as solvents. The crudes were subjected to extensive chromatographic techniques like preparative thin layer chromatography, column chromatography and high performance liquid chromatography (HPLC). A total of six compounds were obtained. Structural elucidation was established through several spectroscopic methods, such as 1D-NMR (1H, 13C, DEPT, NOE), 2D-NMR (COSY,NOESY, HMQC, and HMBC), UV, IR, and MS (GCMS, LCMS and HRMS) and comparison with the published data. Three compounds were isolated from the bark of Ochrosia oppositifolia, one indole alkaloid which is isoreserpiline 1 and two ferulic acid ester namely 2-propenoic acid, 3-(4-hydroxy3,5-dimethoxyphenyl) -,methylester E 73 and 17-methoxy-carbonyl-14- heptadecaenyl- 4-hydroxy-3-methoxy cinnamate F 74. Isolation and purification of alkaloids from the leaves of Ochrosia oppositifolia afforded three indole alkaloids namely neisosposinine 2, reserpinine 3 and alkaloid D 72. All crude extracts and pure compounds were tested for anti plasmodial activity, and the hexane crude of bark showed the highest activity with an IC50 of 0.0505 μg/mL. Among the alkaloids tested, alkaloid D 72 is the most potent compound with an IC50of 0.0123 μmol L-1